Chronic pelvic pain: how does noninvasive imaging compare with diagnostic laparoscopy?. Issue 6 (December 2015) - Tirlapur, Seema A.; Daniels, Jane P.; Khan, Khalid S.
Abstract : Purpose of review: Chronic pelvic pain (CPP) has an annual prevalence of 38/1000 in the UK, with coexisting pathologies often present. Diagnostic laparoscopy has long been the gold standard diagnostic test, but with up to 40% showing no abnormality, we explore the value of noninvasive imaging, such as pelvic ultrasound and MRI. Recent findings: A literature review from inception until January 2015 of the following databases: PubMed, MEDLINE, Cumulative Index to Nursing and Allied Health Literature, Excerpta Medica database, and System for Information on Grey Literature in Europe were performed to identify published studies assessing the usefulness of ultrasound, MRI, and laparoscopy in the diagnosis of CPP. Three studies (194 women) addressed their comparative performance in patients with endometriosis, showing the sensitivity of ultrasound ranged between 58 and 88.5%; MRI was 56–91.5% and in the one study using histology as its reference standard, the sensitivity of laparoscopy was 85.7%. Noninvasive imaging has the additional benefit of being well tolerated, safer, and cheaper than surgery. Summary: CPP, by nature of its multifactorial causation, can be difficult to manage and often requires a multidisciplinary team. Ultrasound and MRI may provide information about the presence or lack of abnormality, which would allow general practitioners or office gynaecologists to initiate treatment and think about surgery as a second-line investigative tool.